2016
DOI: 10.4103/1817-1745.193367
|View full text |Cite
|
Sign up to set email alerts
|

A study of neurosonogram abnormalities, clinical correlation with neurosonogram findings, and immediate outcome of high-risk neonates in Neonatal Intensive Care Unit

Abstract: Background:Neonatal sonography of the brain is now an essential part of newborn care, particularly in high risk and unstable premature infants. Cranial ultrasound is the most available and easily repeatable imaging technique for the neonatal brain showing brain development and the most frequently occurring forms of cerebral injury in the preterm and terms. This study aims to assess the importance of cranial ultrasound as an investigatory modality for high-risk neonates and to find out the morphology of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
3
6
0
2
Order By: Relevance
“…Our results are comparable to Brad way et al study who reported 37% abnormality in early sonography [14]. Most of the other Indian reports have reported incidence of 25.45%, 29.8%, 36%, 38% [5,6,8,15]. However these studies have not specified the exact time of neurosonography.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Our results are comparable to Brad way et al study who reported 37% abnormality in early sonography [14]. Most of the other Indian reports have reported incidence of 25.45%, 29.8%, 36%, 38% [5,6,8,15]. However these studies have not specified the exact time of neurosonography.…”
Section: Resultssupporting
confidence: 76%
“…Previous studies by Bradway et al and Prithviraj et al also reported similar findings with incidence of intraventricular hemorrhage to be 38% and 43% respectively [8,14]. Nagraj et al and Jha et al, two Indian studies reported periventricular echogenicity as the most common finding [5,15].…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations